Breaking the habit in the Covid Era: how is changed the routine of a surgeon in mostly affected italian province, Piacenza, Emilia Romagna - Conti, Luigi; Grassi, Carmine; Banchini, Filippo (Acta Biomedica Atenei Parmensis, 2020)
The Sars-Cov2 Pandemic in Italy gave rise in Piacenza, northern Emilia, to one of the most extensive contagions ever recorded in Italy, the area being hit from the beginning of February, with all its dramatic force and enormous impact in terms of human lives, upsetting social lives. Piacenza is only few kilometers away from what was unexpectedly identified as the first known outbreak in the Western world, registered in Codogno, a small town in the province of Lodi, where the first verified Italian case of the infection Covid– 19 was isolated.Due to the advancement of the contagion and the exponential increase of Covid cases which required hospitalization all the surgical wards of our Hospital, except for the Emergency Surgery of the Hospital’s central hub “Guglielmo da Saliceto” of Piacenza, were converted into Covid wards with various degrees of management care on behalf of the personnel, as also the operating theatres became new ICU units. Consequently, the professional life habits of the surgeons in general have radically changed: the surgeons have been working for about 70% of their working hours in internist support activities for the management of Covid-correlated pneumonia patients.Since then however, many questions have arisen during our daily reflections regarding the need for future planning of our surgery procedures: how much longer can we delay the planning of our selected surgery? Which epidemiological parameters, and other, should we identify in order to start up selected general surgery?For how long can selected surgery be deferred without compromising outcomes and mid to long term mortality in oncological patients in our province, considering also the diagnostic-therapeutic delays in these exceptional months of the Covid era?